Tracheary Element Structure of Some Gymnosperms with Angiosperms: A Comparative Study - Huang , Yuyuan; Han, Yanhua; Wei , Lijun; Wang , Jiazhuo (Research Highlights in Agricultural Sciences Vol. 7, 2023)
This chapter presented comparative studies of vessel types and structure in some gymnosperms and angiosperms. The tissues of the pinna and rachis of Cycas diannaensis and pinna, rachis, and root of Cycas taiwaniana, rachis of Cycas szechuanensis, stem of Metasequoia glyptostroboides (Taxodiaceae), stems of Chamaecyparis obtusa (Sieb.et Zucc.) Endl cv. Tetragona (Cupressaceae), and leaves and stems of Michelia alba and Michelia figo and stems of Amygdalus persica (angiosperms) were compared using scanning electron microscopy. All of these gymnosperm species have perforations in the end walls and lateral walls of their numerous tracheary elements. Certain tracheary components are vessels because they have these structural similarities with angiosperm vessels. Cycads have a variety of vessel types, including spiral and pitted vessels in Chamaecyparis obtusa cv. Tetragona, and pitted vessels in M. glyptostroboides. Cycads, the other two gymnosperms, and the angiosperms all have identical vessel development and structural traits. Some characteristics, such as the extent of incline of the perforated plate in the end wall, demonstrated that some angiosperms had more primitive vessel characteristics than cycads or M. glyptostroboides and C. obtusa cv. Tetragona or glyptostroboides. Numerous of the angiosperms' vessel elements were band-shaped, had no end walls, only two lateral walls, and two margins. The ends of some of these vessel elements are acute with no perforations, while many perforations are only found in the lateral wall.In all species, parenchyma cell walls possessed only a thin primary wall and no perforations, with the exception of tracheae.